Internet-Based Learning System as a Gateway for Educational Development in Nigeria Opportunities and Challenges - R.N.I. , Labaran (African Journal of Education,Science and Technology (AJEST), 2017)
Internet technology is rapidly transforming socio-economic activities for sustainable development and fostering educational opportunities in developing countries. This article discusses the concept of Internet-Based Learning System (IBLS) as an online teaching and learning that provides a cost-effective interactive platform for establishments, students, teachers and administrative personnel to have opportunities to quickly and economically access various standard instructional resources through the Internet on-demand. This reduces expenditures on acquisition and deployment of Information and Communications Technology (ICT) infrastructure and human resources while the telecommunication service providers receive commensurate profits on their investments. The article focuses on the M-Learning, E-Learning and identifies some critical barriers for Internet-based learning in Nigerian education system which include weak Information Technology (IT) policies, inadequate funding, lack of political will, high tax duties, and poor infrastructure which culminated in poverty, unemployment, spread of diseases, cybercrimes, prostitution, industrial strikes, insecurity, “Boko Haram”, brain drain, and corruption. It also identifies the opportunities of its adoption for educational value in Nigerian institution of learning. It concludes by offering recommendations that can help ameliorate the challenges raised, especially the need for joint effort, adequate funding, political will, partnerships through public private partnership initiative, adequate sponsorship like scholarship, research, provisioning for loan facilities with minimum interest rates, tax and custom duties reduction on importation of ICT equipment.